Guía fotográfica de fauna y flora representativa de la comunidad del Placer y San Pedro, cantón Baños de Agua Santa. - Cacuango Rosero, Edwin Sebastián (2021)
Placer and San Pedro's community are strategic points for biodiversity because they are tributaries to the ecological corridor Llanganates-Sangay included in the low montane evergreen forest ecosystems. A photographic guide of representative fauna and flora was developed to expose and highlight the diversity of existing wildlife species so that visitors or the general public have a photographic-descriptive material as a tool for dissemination and knowledge. For which 3 study zones were established based on the vegetation cover and the diverse recommendations of the residents for the sites of most significant interest for the registration of species found in the different routes called: Z1: "La Nueva Libertad", Z2: "Cascada Amarilla" and Z3: "San Pedro Community", biological monitoring techniques were applied for the registration and identification of the same by performing tours along the trails already established with schedules and observation stops according to the need of each of the biological groups, in the case of fauna the mammalian, ornithofauna and herpetofauna were evaluated, while in the case of flora different plant strata were evaluated with the most essential or striking plants for the communities according to the considerations of the local guides. As a result, 68 species of birds, five species of amphibians, five reptile’s species, and four species of mammals were obtained, and 39 species of flora were collected. The botanical samples were properly herborized and are kept in the herbarium of the Technical University of Cotopaxi. The guide includes taxonomic information, conservation status, photographs, descriptions, and a distribution map. Based on the work carried out, positive results were obtained by presenting extensive lists of wild species, contributing to the development of environmental interpretation activities with the inhabitants and tourists, promoting the appreciation and appropriation of the resources, and promoting conservation research that effectively contributes to community development.